Evaluación de la calidad exportable de racimos de banano tratados con protectores biodegradables e infusión de laurel rosado (nerium oleander) - Gabino Torres, Cristhian Eduardo (Machala : Universidad Técnica de Machala, 2019)
Banana is considered one of the most consumed crops worldwide, being the fourth most cultivated species, which generates foreign exchange and employment sources to the countries that produce and export it. For the protection of the fruit in the field, materials such as plastic covers, bow ties, daipas and basmer protectors (nun's neck) are used, with the purpose of preventive quality of the clusters, and that allow diminishing the losses by insects, birds, and damage during the harvesting and packaging processes, to obtain a greater number of boxes and fruit of better quality. Plastics being slow degradation cause pollution outside or inside the banana, water sources contaminate drains, irrigation canal, among other sites, causing pollution of the environment. Ecuador is characterized by being the main producer and exporter, covering the demand of countries such as Russia and the United States, creating competition with other producing countries to reach those markets with fruit of agronomic and aesthetic quality at the lowest cost and with the least environmental impact. Taking into account the above, the investigation was carried out with the purpose of evaluating the effect of the infusion of pink Laurel (Nerium oleander L.) impregnated in biodegradable protectors made of bijao leaves (Calathea lutea Aubl. Schult.). On the quality Exportable banana bunches, applied in a conventional banana crop of the farm "La Carmela" that has 16.8 ha, located in the province of El Oro, Machala canton, parish "El Retiro". A completely randomized block design (BCA) was used, with 4 treatments, 5 repetitions and 3 replicas, making a total of 60 plants to evaluate, in plots of 0.8 ha: T1 (Organic protector + infusion); T2 (Nun neck protector + Bullet 55); T3 (Organic Protector); T4 (Nun neck protector). For the statistical analysis of the quantitative and qualitative variables, ANOVA, homogeneity of variance and Chi-square was used, with the statistical package IBM - SPSS Statistics editor version 22 for Windows at 95% reliability. According to the analysis of variance, the variables cochineal presence and presence of red spot did pests affect the only ones that presented significant differences, highlighting the T1 as the treatment least, this quality being due to the high residual spectrum of the pink Laurel. The T1 and T3 obtained higher means in the variables: Brix degrees, cluster weight, rachis, fruit and ratio. Also, that cut days were cut. Almond with a white quality was repeated in greater numbers in T1, on the contrary, T4 was the treatment with less heavy clusters, with lesser degree of its fruit and which the greatest number of pests affected. Damages that can occur in the fingers, such as spike damage or handling damage during the harvest of the cluster, had a greater incidence, although not significantly, in T1 and T3. The T2 in the length of the finger of the second hand obtained a higher average; on the contrary, the T1 and T4 had a similar average in the length of the finger of the last hand.
El banano es considerado uno de los cultivos de mayor consumo a nivel mundial, siendo la cuarta especie más cultivada, lo que genera divisas y fuentes de empleo a los países que lo producen y exportan. Para la protección de la fruta en el campo, se utiliza materiales como las fundas plásticas, corbatines, daipas y protectores basmer (cuello de monja), con el propósito de calidad preventiva de los racimos, y que permiten disminuir las mermas por insectos, pájaros, y estropeos durante los procesos de cosecha y empaque, para la obtención de mayor número de cajas y fruta de mejor calidad. Los plásticos al ser de lenta degradación causan contaminación fuera o dentro de la bananera, contaminan fuentes de agua los drenajes, canal de riego, entre otros sitios, provocando la contaminación del medio ambiente. Ecuador se caracteriza por ser el principal productor y exportador, cubriendo la demanda de países como Rusia y Estados Unidos, creando una competencia con otros países productores por llegar a esos mercados con fruta de calidad agronómica y estética al menor costo y con el menor impacto ambiental. Tomando en consideración lo expuesto, la investigación se realizó con el propósito de evaluar el efecto de la infusión de Laurel rosado (Nerium oleander L.) impregnado en protectores biodegradables hechos de hojas de bijao (Calathea lutea Aubl. Schult.), sobre la calidad exportable de racimos de banano, aplicados en un cultivo de banano convencional de la finca “La Carmela” que cuenta con 16.8 ha, situada en la Provincia de El Oro, cantón Machala, parroquia “El Retiro”. Se usó un diseño de bloques completamente al azar (BCA), con 4 tratamientos, 5 repeticiones y 3 réplicas, haciendo un total de 60 plantas a evaluar, en parcelas de 0.8 ha: T1 (Protector orgánico + infusión); T2 (Protector cuello de monja + Bala 55); T3 (Protector orgánico); T4 (Protector cuello de monja). Para el análisis estadístico de las variables cuantitativas y cualitativas, se utilizó ANOVA, homogeneidad de varianza y Chi-cuadrado, con el paquete estadístico IBM - SPSS Statistics editor versión 22 para Windows a una confiabilidad del 95%. De acuerdo al análisis de varianza, las variables presencia de cochinilla y presencia de mancha roja, fueron las únicas que presentaron diferencias significativas, destacando el T1 como el tratamiento menos afectado por plagas, debiéndose esta cualidad, al alto espectro residual del Laurel rosado. El T1 y T3 obtuvieron medias mayores en las variables: grados Brix, peso del racimo, raquis, fruta y ratio. Además, que se disminuyó los días de corte. La almendra con una calidad de blanca se repitió en mayor número en T1, por el contrario, el T4 fue el tratamiento con racimos menos pesados, con menor grado de su fruta y que se vio afectado por el mayor número de plagas. Los daños que se pueden presentar en los dedos, como daño de punta o estropeos por manipulación durante la cosecha del racimo, tuvieron mayor incidencia, aunque no significativamente, en el T1 y T3. El T2 en la longitud del dedo de la segunda mano obtuvo una media superior, por el contrario, el T1 y T4 tuvieron una media semejante en la longitud del dedo de la última mano.
Keywords: MANCHA; ROJA; CLÚSTER; PREVENTIVA